How Financial Performance, CSR Disclosure, and GCG Mechanism in Indonesia and Malaysia Banks? - Brigitta Eva Sinta Amartya; Wahdan Arum Inawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The goals of this study is to ascertain the simultaneous or partial effects of corporate social responsibility disclosure, board size, managerial ownership, and institutional ownership. The population in this study are banking sub-sector companies listed on the Indonesia Stock Exchange and Malaysia Stock Exchange in 2017-2022. The sample selection in this study used a purposive sampling method. The samples obtained were 12 Indonesian banking companies and 6 Malaysian banking companies. The data analysis used is descriptive and panel data regression. Based on the research results, the banks listed on the Indonesia Stock Exchange show that CSR disclosure, board size, and managerial ownership do not affect financial performance and institutional ownership positively affects financial performance. Meanwhile, the banking sub-sector companies listed on the Malaysia Stock Exchange show that CSR disclosure, board size, managerial ownership, and institutional ownership do not affect financial performance